Spin injection and magnetoresistance in MoS2-based tunnel junctions using Fe3Si Heusler alloy electrodes - SANVITO, STEFANO; Rotjanapittayakul, Worasak; Pijitrojana, Wanchai; Archer, Thomas; Prasongkit, Jariyanee (My University, 2018)
Recently magnetic tunnel junctions using two-dimensional MoS2 as nonmagnetic spacer have been fabricated, although their magnetoresistance has been reported to be quite low. This may be attributed to the use of permalloy electrodes, injecting current with a relatively small spin polarization. Here we evaluate the performance of MoS2-based tunnel junctions using Fe3Si Heusler alloy electrodes. Density functional theory and the non-equilibrium Green’s function method are used to investigate the spin injection efficiency (SIE) and the magnetoresistance (MR) ratio as a function of the MoS2 thickness. We find a maximum MR of ~300% with a SIE of about 80% for spacers comprising between 3 and 5 MoS2 monolayers. Most importantly, both the SIE and the MR remain robust at finite bias, namely MR > 100% and SIE > 50% at 0.7 V. Our proposed materials stack thus demonstrates the possibility of developing a new generation of performing magnetic tunnel junctions with layered two-dimensional compounds as spacers
Keywords: Magnetic tunnel junctions; MoS2; Spin-injection efficiency; Magnetoresistance